2021
DOI: 10.1186/s12906-021-03405-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Lactobacillus casei Shirota against both Candida auris and Candida spp. isolates that cause vulvovaginal candidiasis and are resistant to antifungals

Abstract: Background Vulvovaginal candidiasis (VVC), the second leading cause of genital infection in women of reproductive age, is caused by yeasts of the genus Candida. Treatment is usually empirical and performed with azoles, which have shown increasing ineffectiveness due to resistance from these species. This therapeutic challenge has led to the search for new treatment strategies. Lactobacillus spp. produce several components with microbicidal effects, such as lactic acid. These species are the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…A study by Camile Nina et al (2019) revealed that lactic acid, in combination with major peptidoglycan hydrolase released by L. rhamnosus, GG successfully inhibits the hyphal formation of C. albicans [104]. Paniágua et al (2021) also reported that C. albicans' hyphae development was significantly hampered by L. casei Shirota [105]. C. albicans was found to modulate low pH into an alkaline condition to undergo hyphal formation, thus, in a way, supporting the idea that vaginal acidic condition is an inhibitory mechanism against the morphological transition in C. albicans [106].…”
Section: Interaction Between Lactobacillus and Candidamentioning
confidence: 99%
“…A study by Camile Nina et al (2019) revealed that lactic acid, in combination with major peptidoglycan hydrolase released by L. rhamnosus, GG successfully inhibits the hyphal formation of C. albicans [104]. Paniágua et al (2021) also reported that C. albicans' hyphae development was significantly hampered by L. casei Shirota [105]. C. albicans was found to modulate low pH into an alkaline condition to undergo hyphal formation, thus, in a way, supporting the idea that vaginal acidic condition is an inhibitory mechanism against the morphological transition in C. albicans [106].…”
Section: Interaction Between Lactobacillus and Candidamentioning
confidence: 99%
“…A recent study found LA at low pH neither enhanced nor inhibited the growth of Candida spp. ( 55 ) while another study ( 56 ) reported that LA inhibits seven different Candida spp. with a minimal inhibitory concentration of 2.5 mg/ml (0.25%).…”
Section: Discussionmentioning
confidence: 98%
“…The hyphae enlarge in millimeters with increasing time and consecutively form hyphal tips [77]. C. albicans pathogenesis is promoted by hyphal growth [78]. Morphogenesis of the yeast to a fungal state encourages virulence by targeting host immune cells ( i.e ., macrophage and complement proteins) [79].…”
Section: Discussionmentioning
confidence: 99%